The Relevance of Kuntowijoyo's Prophetic Sociology in the Concept of Social Studies Learning at Al Mustaqim Islamic Boarding School (Study of Humanist Thought) - Susanto, Andika; Anwar, Anwar (CV. DYOQU PUBLISHING MANAGEMENT, 2025)
Background:Social Studies (IPS) learning in Islamic boarding schools (pesantren) has unique characteristics that integrate moral, social, and spiritual values. However, empirical studies on how the prophetic values ​​of humanization, liberation, and transcendence are implemented in IPS learning are still limited. Aims:This study aims to analyze the implementation of social studies learning at Al-Mustaqim Islamic Boarding School and examine its relevance to Kuntowijoyo's Prophetic Sociology concept. Methods:The research used a qualitative approach through observation, in-depth interviews with the madrasah principal, social studies teachers, and students, and documentation. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data presentation, and drawing conclusions. Result:The research results show that social studies learning in Islamic boarding schools has integrated humanization values ​​through dialogic learning, liberation through developing social awareness and the role of students as agents of change, and transcendence through linking social studies material to Islamic teachings. This integration of prophetic values ​​creates holistic, contextual learning, oriented toward the formation of social and religious character. Conclusion:Social studies learning at Al-Mustaqim Islamic Boarding School is relevant to the Prophetic Sociology paradigm and aligned with global education theory. This model has the potential to be an effective approach to character education and can be replicated in other faith-based educational institutions.